Metodologias ativas e compromisso ético na formação em psicologia - Bereta, Thaísa Angélica Déo da Silva (Editora Oficina Universitária, 2022)
Who is the psychologist we want to form? This question was part of my master's work, almost thirty years ago. Today, in this book, this question continues to be present, with new contributions. The study of active methodologies in university education for the education of critical and reflective professionals, capable of understanding the dimension of their work in a broader way, is more than relevant; she is essential. In this book, trainers of professionals in the area of Psychology will find a broad analysis of the pedagogical projects and curriculum frameworks of Psychology courses in the state of São Paulo and a broad bibliographical survey on the use of active methodologies in the training of psychologists. In her work, Thaísa sought disciplines related to Ethics, Public Policies, Human Rights and Affirmative Policies in psychologist training, as she understands that such themes need to be present intentionally and not occasionally in university education. Finally, I emphasize that his analysis of the academic environment draws attention to the importance of the student's active role in their training, in addition to the need to offer opportunities for directed reflection and theoretical-practical activities that enable the construction of know-how that goes beyond the theoretical and technical, in a word, the construction of an ethical practice. It is with joy that I present another work by my colleague Thaísa to the public interested in doing Psychology better. PATRICIA UNGER RAPHAEL BATAGLIA